Reason to change : a rational emotive behaviour therapy workbook 2nd edition - Dryden, Windy (New York, NY : Routledge, 2021)
"Rational Emotive Behaviour Therapy (REBT) is an approach to counselling and psychotherapy in which great emphasis is placed on how attitudes are at the root of emotional problems and their solution. The first edition of Reason to Change was written as a one-of-a-kind workbook teaching the practical skills of REBT. In this updated edition, Windy Dryden teaches, in a very specific way, the skills needed to use this therapeutic approach in practice in a thorough and accessible way. Each skill is explained in detail, and examples are given of how each skill can be put into practice. These skills include: developing a problem list and setting goals choosing a target problem and assessing a specific example questioning attitudes dealing with your doubts, reservations and objections taking action. By using these skills in an active way, it can be possible to overcome emotional problems such as anxiety, depression, shame, guilt, hurt, unhealthy anger, unhealthy jealousy and unhealthy envy. This book can be used by people on their own, and by those who are consulting an REBT therapist. It will also be of interest to therapists and counsellors"--
Revised edition of the author's Reason to change, 2001.
Keywords: Rational emotive behavior therapy; PSYCHOLOGY / Psychotherapy / Counseling; PSYCHOLOGY / Mental Health